2023
DOI: 10.1128/spectrum.04091-22
|View full text |Cite
|
Sign up to set email alerts
|

What’s the Matter with MICs: Bacterial Nutrition, Limiting Resources, and Antibiotic Pharmacodynamics

Abstract: For studies of antibiotics and how they work, the most-often used measurement of drug efficacy is the MIC. The MIC is the concentration of an antibiotic needed to inhibit bacterial growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…We found that even though these mutants are resistant, their growth rates and the maximum optical densities decreased proportionally to the drug concentration and their lag time was substantially increased (Supplemental Figure 4). This result is consistent with previous observations 15 .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…We found that even though these mutants are resistant, their growth rates and the maximum optical densities decreased proportionally to the drug concentration and their lag time was substantially increased (Supplemental Figure 4). This result is consistent with previous observations 15 .…”
Section: Resultssupporting
confidence: 94%
“…We exposed four independent cultures of ∼10 5 CFU/mL of E. coli MG1655 in glucose-limited minimal media to super-MIC (Minimum Inhibitory Concentration) concentrations of CHL and AZM for 30 days (Figure 1). The MIC of CHL and AZM with MG1655 were estimated by broth microdilution in this glucose-limited minimal media and found to be 6.25 ug/mL for both drugs 13 . Super-MIC concentrations of each drug that were shown to be bacteriostatic with minimal killing and/or growth were used in the experiment (Supplemental Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…S3). These results are consistent with those previously observed for Escherichia coli [6], demonstrating that the results obtained previously are not restricted to Gram-negative bacteria.…”
Section: Resultssupporting
confidence: 93%
“…Previous studies have revealed that exposing E. coli to sub-inhibitory concentrations of antibiotics leads to decreasing both maximum growth rate and maximum optical density while increasing the lag phase of growth [6]. Our results here confirm this phenomenon applies to S. aureus as well.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation